Risk Factors for Patellar Luxation in Dogs in the Philippines - Oronan, Rey Barcenas; Nacion, Camille Sophia; Calibo, Matthew Benedict (Media Kedokteran Hewan, 2023)
A retrospective case-control study was conducted on dogs with patellar luxation who presented to the Veterinary Teaching Hospital Diliman Station-Companion Animal Clinic between January 1, 2010, and December 31, 2019. There was a total of 73 dogs were diagnosed with patellar luxation. The majority of the dogs presented with limping, and the causes were mostly unknown. Unilateral medial patellar luxation was the most common type (21.92%). The average age of patients with patellar luxation was 3.24 years old. Puppies are 0.03 less likely to be diagnosed with patellar luxation, while juveniles are 3.74 times more likely, and mature adults are 2.19 times more likely to be diagnosed. The affected dogs included intact males (47.95%), neutered males (4.11%), and intact females (47.95%). The average weight of the affected dogs was 8.39 kg and the majority (35.62%) had a body condition score of 5/9. The Pomeranian was the most common breed for patellar luxation, followed by the mixed breed Shih Tzu, Toy Poodle, and Chihuahua. Mixed breeds are 0.39 times less likely, and dogs fed with dry dog food are 0.51 times less likely to develop the condition. Age and breed were also significantly associated with patellar luxation.